KnowledgeBoat Logo

Mathematics

Find the mean proportion between aba+b and a2b2a2b2\dfrac{a - b}{a + b} \text{ and } \dfrac{a^2b^2}{a^2 - b^2}.

Ratio Proportion

3 Likes

Answer

Let mean proportion between aba+b and a2b2a2b2\dfrac{a - b}{a + b} \text{ and } \dfrac{a^2b^2}{a^2 - b^2} be x.

aba+bx=xa2b2a2b2x2=aba+b×a2b2a2b2x2=(a2b2)(ab)(a+b)(a2b2)x2=(a2b2)(ab)(a+b)(ab)(a+b)x2=a2b2(a+b)2x=a2b2(a+b)2x=aba+b.\therefore \dfrac{\dfrac{a - b}{a + b}}{x} = \dfrac{x}{\dfrac{a^2b^2}{a^2 - b^2}} \\[1em] \Rightarrow x^2 = \dfrac{a - b}{a + b} \times \dfrac{a^2b^2}{a^2 - b^2} \\[1em] \Rightarrow x^2 = \dfrac{(a^2b^2)(a - b)}{(a + b)(a^2 - b^2)} \\[1em] \Rightarrow x^2 = \dfrac{(a^2b^2)(a - b)}{(a + b)(a - b)(a + b)} \\[1em] \Rightarrow x^2 = \dfrac{a^2b^2}{(a + b)^2} \\[1em] \Rightarrow x = \sqrt{\dfrac{a^2b^2}{(a + b)^2}} \\[1em] \Rightarrow x = \dfrac{ab}{a + b}.

Hence, mean proportion between aba+b and a2b2a2b2 is aba+b\dfrac{a - b}{a + b} \text{ and } \dfrac{a^2b^2}{a^2 - b^2} \text{ is } \dfrac{ab}{a + b}.

Answered By

1 Like


Related Questions